Environmental protection of international watercourses under international law - McIntyre, Owen. (Aldershot, England ; Burlington, VT : Ashgate, 2007)
McIntyre's work explains the legal means by which requirements of environmental protection influence the determination of a reasonable and equitable regime for allocating rights to riparian states to utilize shared freshwater resources.
8 Environmental Protection of International Watercourses II: Procedural Rules of Customary and General International Law9 Conclusion: Environmental Protection as a Factor in Determining the Equitable Utilization of International Watercourses; Bibliography; Index
Description based upon print version of record.
Includes bibliographical references (p. [381]-411) and index.
English
Description based on publisher supplied metadata and other sources.
Keywords: International rivers; Water rights (International law); Water -- Pollution -- Law and legislation; Water resources development -- Law and legislation; Liability for water pollution damages; Electronic books